Hyperplastic Polyps Discovered Because of Unprovoked Acute Upper Gastrointestinal Bleeding as an Unusual Presentation of Malignancy - Lakshmi Kannan; Mwangi Kamau (Annals of Internal Medicine: Clinical Cases)
Gastric hyperplastic polyps are small (<1 cm), asymptomatic, and found incidentally on esophagogastroduodenoscopy. Patients can present with dyspepsia, abdominal pain, anemia from chronic occult bleeding, and, rarely, acute upper gastrointestinal bleeding. Helicobacter pylori, autoimmune gastritis, and long-term use of proton-pump inhibitors can increase the risk for hyperplastic polyps. Dysplasia and carcinoma in the surrounding gastric mucosa with concomitant hyperplastic polyps can be seen but carcinoma and dysplasia within the hyperplastic polyp itself are extremely rare. We report on a 70-year-old White woman who presented with melena from what appeared to be hyperplastic polyps on esophagogastroduodenoscopy, but pathology reported frank intramucosal adenocarcinoma.